A dehydrative glycosylation protocol mediated by nonafluorobutanesulfonyl fluoride (NfF). (8th January 2021) - Tang, Yu; Reddy, D. Prabhakar; Yu, Biao
Abstract: A new dehydrative glycosylation protocol that proceeds through selective activation of glycosyl hemiacetals with nonafluorobutanesulfonyl fluoride (NfF) has been disclosed. Contrary to the major classical glycosylation reactions that proceed under acidic or neutral conditions, the present glycosylation reaction proceeds under mild basic conditions. In the absence of an external acceptor, self-condensation of the glycosyl hemiacetal occurs, providing the corresponding symmetrical 1, 1′-disaccharides in high yields. Graphical abstract: Image 1